O campo da História da Educação no Brasil: um estudo baseado nos grupos de pesquisa - Hayashi, Carlos Roberto Massao (Universidade Federal de São Carlos, 2007)
This study is about the field of the History of Education in Brazil and it was based on the analysis of the research groups that integrate the Directory of Research Groups in Brazil/CNPq, in order to verify its contribution for the consolidation of this research area in the country. The criterion for the recognition of group integrant of the critical mass in History of the Education was the development, at least, of a research line in this area, as defined for the group leader. The methodology was developed in the following stages: 1) literature review on the research in education in Brazil with focus on the History of the Education; 2) data retrieval in the Directory of Research Groups in Brazil/CNPq for identification of the research groups and in the Lattes Platform Résumé for recovery of the scientific production of the research groups leaders; 3) description and categorization of the retrieved data and 4) analysis and interpretation of the results achieved through the bibliometrical approach. For the development of the methodology, a software of bibliometrical analysis was used, and that had as objective to identify the characteristics of the research groups of the area of Education, consisting of the following aspects: a) area of knowledge; b) year of creation; b) leadership; c) research lines; d) composition (researchers, students and technicians); e) repercussions of the group activities; f) scientific and technological production; g) region; h) institutional entailing; i) scientific collaboration. The results achieved in the censused base 2004 of the Directory of Research Groups/CNPq had identified the existence of 108 groups and 317 research lines. The analyses allowed to delineate the scientific activities of the research groups in History of the Education, its geographic and institutional distribution, the subjects of research, the standards of the spreading of results of the researches and the social relevance of the realized researches. The retrieved data were collated with the theoretical review objectifying to guarantee validity and fidelity in its interpretation.
The field of History of Education in Brazil: a study based on the research groups
Keywords: Educação; História da educação; Análise bibliométrica; Produção científica; Education; History of education; Bibliometric analysis; Scientific production; CIENCIAS HUMANAS::EDUCACAO